Dysautonomia, a Heuristic Approach to a Revised Model for Etiology of Disease. Issue 1 (2009) - Lonsdale, Derrick
Abstract : Dysautonomia refers to a disease where the autonomic nervous system is dysfunctional. This may be a central control mechanism, as in genetically determined familial dysautonomia (Riley-Day Syndrome), or peripherally in the distribution of the sympathetic and parasympathetic systems. There are multiple reports of a number of different diseases associated with dysautonomia. The etiology of this association has never been explained. There are also multiple publications on dysautonomia associated with specific non-caloric nutritional deficiencies. Beriberi is the prototype of autonomic dysfunction. It is the best known nutritional deficiency disease caused by an imbalance between ingested calories and the vitamins required for their oxidation, particularly thiamin. Long thought to be abolished in modern medical thinking, there are occasional isolated reports of the full-blown disease in developed Western cultures. Apart from genetically and epigenetically determined disease, evidence is presented that marginal high calorie malnutrition, particularly with reference to simple carbohydrates, is responsible for widespread dysautonomia. The brain and heart are the organs that have a fast rate of oxidative metabolism and are affected early by any mechanism that reduces oxidative efficiency. It is hypothesized that this results in a chaotic state of the hypothalamic/autonomic/endocrine axis. Due to the lack of adequate automatic controls, this may be responsible in some cases for breakdown of organ systems through long-standing energy deficiency, thus leading eventually to organic disease.